EFIKASI DIRI DAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN WORK LIFE BALANCE MAHASISWA PEKERJA - Amini, Soleh; Widi, Devi Aprilia Permata (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2024)
Work-life balance is a condition where a person can manage and divide time and energy for work and personal life well. Work-life balance is a person's ability to manage and divide time in a balanced way in work and personal life. This study aims to determine the relationship between self efficacy and peer social support with work-life balance. The research method applied in this study is a quantitative method. The population in this study were students of the Muhammadiyah University of Surakarta who were working. The sampling technique used purposive sampling with the characteristics of active undergraduate students of the Muhammadiyah University of Surakarta, aged 18-25 years, female and male, working while studying, having a minimum working hour of 6 hours per day, having worked for at least 1 month, working in the Surakarta area, and not married. The sample in the study amounted to 100 students. Data collection used a psychological measurement scale, namely the work-life balance scale, selfefficacy, and peer social support. Data analysis used multiple linear regression test analysis. The results of this study indicate that there is a significant relationship between self-efficacy and peer social support with work-life balance. The ability to balance roles in personal life and work is greatly influenced by the individual's self-confidence and support from the people around him, thus enabling the individual to achieve satisfaction in balancing his life.